Observer based adaptive control for optical manipulation of cell - Li, X. (2013)
In this paper, an observer based adaptive control method is proposed for optical manipulation of cell. The dynamics of the robotic manipulator of the laser source is introduced in the optical tweezers system, so that a closed-loop control method is formulated and solved, and a backstepping approach is used to derive a control input for the manipulator. The interaction between the cell dynamics and the manipulator dynamics leads to a fourth-order overall dynamics, and hence a nonlinear observer is constructed to avoid the use of high-order derivatives of the positions in the control input. Stability of the closed-loop system is analyzed by using Lyapunov-like analysis. Simulation results are presented to illustrate the performance of the proposed control methods.